Poučevanje predmeta šport z vidika kompetenc razrednih učiteljev - Planinšec, Jurij; Matejek, Črtomir (Revija za elementarno izobraževanje, 2020)
The Physical Education Teaching in Terms of the Elementary Teachers' Competencies. The main aim of this study was to find out how elementary teachers evaluate their competence for teaching Physical Education (PE) regarding seniority and physical activity involvement. The study was conducted on a non-randomized sample of 220 elementary teachers teaching PE. The results show that the highest assessed competences include the ability to plan, organize, implement and evaluate sports lessons. Teachers rated as lowest those competencies related to integrating and working with children with special needs in PE lessons.
Keywords: sports, teachers, professional training, professional development, subjectspecific competences